2022
DOI: 10.1111/exd.14537
|View full text |Cite
|
Sign up to set email alerts
|

Mutations within the putative protease domain of the human FAM111B gene may predict disease severity and poor prognosis: A review of POIKTMP cases

Abstract: Hereditary fibrosing poikiloderma with tendon contractures, myopathy and pulmonary fibrosis (POIKTMP) is a unique multi-systemic fibrosing and autosomal dominant genetic syndrome. The development of poikiloderma is one of the earliest signs of this disorder. 1 Consequently, this disease is often misdiagnosed in infants and neonates as Rothmund-Thomson syndrome (RTS), Bloom syndrome, dyskeratosis congenita, Baller-Gerold syndrome, poikiloderma neutropenia, Weary syndrome and Kindler syndrome. 1 Clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…The same mutation could lead to different phenotypes and an association between genotypes and phenotypes was not established ( Mercier et al, 2013 ; Mercier et al, 2015 ; Goussot et al, 2017 ), suggesting that other factors, such as racial factor and environmental variables, might influence the clinical characteristics of this disease. To date, including our case in the present study, a total of 37 patients with this rare disorders have been reported globally ( Arowolo et al, 2022a ). For patients with congenital poikiloderma, the predominant manifestation is early onset poikiloderma, telangiectasia, and epidermal atrophy.…”
Section: Discussionmentioning
confidence: 89%
“…The same mutation could lead to different phenotypes and an association between genotypes and phenotypes was not established ( Mercier et al, 2013 ; Mercier et al, 2015 ; Goussot et al, 2017 ), suggesting that other factors, such as racial factor and environmental variables, might influence the clinical characteristics of this disease. To date, including our case in the present study, a total of 37 patients with this rare disorders have been reported globally ( Arowolo et al, 2022a ). For patients with congenital poikiloderma, the predominant manifestation is early onset poikiloderma, telangiectasia, and epidermal atrophy.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, an important new insight with implications for genotype-phenotype correlation was recently reported. Arowolo et al suggested that patients with mutations within the putative protease domain of the FAM111B protein may have higher disease burden and poorer prognoses compared to patients with mutations outside the domain ( Arowolo et al, 2022 ). Among the reported causative mutations in FAM111B, all except three are within this domain ( Figure 2C ), as is the present mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients develop pulmonary fibrosis, which has been reported to lead to poor prognosis. In a previous review, only symptomatic therapy was recommended for those with respiratory failure ( Arowolo et al, 2022 ). Only two patients with POIKTMP have been reported to be treated for pulmonary involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the human FAM111B gene are also associated with a rare multisystemic fibrosing disease-poikiloderma, tendon contracture, myopathy, and pulmonary fibrosis (POIKTMP, which is the adopted terminology for this disease) (1)(2)(3)(4). FAM111B gene mutations are also implicated in other clinical manifestations such as progressive osseous heteroplasia (POH) (5), autism spectrum disorders (6), modification of genes associated with cognitive development (7), nevus of Ota with choroidal melanoma (8), and mutations of unknown clinical significance/common genetic polymorphism (9).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overexpression of this gene in cancer cells is associated with increased cancer progression and poor clinical outcomes ( 13 16 ). Although there are about 19 reported FAM111B mutations ( Supplementary Table 1 ) to date ( 3 5 , 10 , 12 , 17 24 ), the physiological function(s) of the FAM111B protein and its dysfunctional role in diseases like fibrosis and cancers are not well established.…”
Section: Introductionmentioning
confidence: 99%